Exploring Generation Z's Perspective on Twitter as a News Discovery Platform: Insights from @CNNIndonesia Followers: Menelusuri Perspektif Generasi Z tentang Twitter sebagai Platform Pencarian Berita: Wawasan dari Pengikut @CNNIndonesia - Syafrilla Ainayatul Rifhan; Poppy Febriana (Academia Open, 2024)
This qualitative descriptive research aims to explore how Generation Z perceives the use of Twitter, particularly the @CNNIndonesia news account, as a platform for news discovery. Employing purposive sampling, in-depth interviews, and observations, the study reveals that followers retain knowledge obtained from @CNNIndonesia, emphasizing the critical role of perception indicators in influencing their attitudes. The informants express a preference for @CNNIndonesia, citing its reliability and alignment with their information needs. The results underscore the significance of perception in shaping user behavior on Twitter as a news source. Highlights : Digital Information Consumption: Explore how Generation Z consumes and retains news information through the Twitter platform, specifically focusing on the @CNNIndonesia account. Perception Indicators: Investigate the key indicators shaping the perceptions of Generation Z followers towards @CNNIndonesia as a reliable and preferred news source. User Behavior Influence: Highlight the significance of perception in influencing the behavior of Generation Z users on Twitter as they seek and engage with news content. Keywords: Generation Z, Twitter, News Discovery, @CNNIndonesia, Perceptions